Real-Time Continuous Glucose Monitoring Reduced Costly Diabetes-Related Events in Adolescents and Young Adults despite Lack of Short-Term Reduction in Hemoglobin A1c. (11th April 2023) - Beck, Joni K.; Allen, Rebecca A.; Jeter, Kathryn M.; Fisher, Rachel S.; Dattilo, Taylor M.; Traino, Katherine A.; Anderson, Michael; Cutler, James; Sparling, David P.
Abstract : Real-time continuous glucose monitoring (rtCGM) can directly improve patient outcomes, including decreased health care system utilization and associated costs. The purpose of this study was to evaluate the clinical benefits of rtCGM use in a high-risk, under-resourced cohort of adolescents and young adults (AYA) with type 1 diabetes (T1D) who had no prior access to rtCGM. The effects of rtCGM use on hemoglobin A1c (A1c) and the frequency of health care events (i.e., diabetes-related emergency room (ER) visits, hospitalizations, emergency medical services (EMS), and after-hour emergency calls) were evaluated regarding payor costs in 33 AYA with ≥70% rtCGM use. Secondary aims included the evaluation of a phone-based pattern management intervention. The frequency of health care events decreased at 12 and 24 weeks for all participants, and there was no significant difference by treatment group. We estimated that the use of rtCGM in this cohort results in a projected annualized cost-savings of $195, 943 to $294, 864 or 43–65% per year based on Medicare or list pricing for rtCGM, respectively. Results also revealed improvements in A1c at 12 weeks for all study participants, but this was not maintained at 24 weeks for the phone-based pattern management intervention group. Our findings suggest that rtCGM may be an effective tool for reducing diabetes-related events and underscores the importance of access. Future studies are needed to further examine tailored interventions and support to optimize rtCGM use and glycemic health in high-risk AYA.